Challenges and Teaching Materials in English for Young Learners in Sweden - Nilsson, Maria (Educare, 2024)
Recent European studies in the field of primary English education identify a number of challenges related to language development, motivation, and diversity of proficiency levels among learners. Nevertheless, early language instruction remains under-researched. The current study investigates challenges perceived by Swedish primary teachers of English and their thoughts and experiences regarding teaching materials. The study takes a special interest in picturebooks because they are often foregrounded as useful resources for promoting both motivation and language learning. Quantitative and qualitative data were collected through an online questionnaire with 109 Swedish teachers for school years F–6. The findings reveal that the substantial heterogeneity of proficiency levels among learners is the biggest challenge facing teachers. In addition, the teachers reported challenges related to this diversity, such as a shortage of teaching materials to cater to varying needs and difficulties in engaging all learners in oral language production. Teaching materials used often comprise downloaded resources, coursebooks, or YouTube clips. Although many teachers are positive toward the potential of picturebooks as an instructional resource, most reported not using them. The findings are discussed in relation to the goals of early English instruction, the current understanding of young language learners, and communicative language teaching.